Cytoreductive surgery for metastatic gastrointestinal stromal tumors treated with ripretinib: A single-center experience - Zhaoming Guan; Shaohua Yang; Kaiyu Sun; Yihang Shi; Yun Feng; Shirong Cai; Xinhua Zhang; Yulong He (Clinical Surgical Oncology, 2023)
Background: Cytoreductive surgery (CRS) has been advocated as an additional treatment with survival benefits for advanced gastrointestinal stromal tumor (GIST), especially in patients with responsive disease or focal progression after treatment with imatinib. Ripretinib is a fourth-line therapy for advanced GIST. This single-center pilot study investigated the short-term safety and efficacy of CRS after treatment with ripretinib in selected patients with recurrent or metastatic GIST. Methods: Medical records of patients with recurrent or metastatic GIST who underwent CRS after ripretinib in the First Affiliated Hospital of Sun Yat-sen University between June 1st, 2020 and June 1st, 2022 were retrospectively reviewed. Patients’ clinicopathological characteristics, preoperative treatment and general condition, surgical information, and postoperative management were recorded. Results: This study included 7 patients who underwent CRS after ripretinib. Radiographic response to ripretinib included partial response (n ​= ​1), stable disease (n ​= ​5), and progressive disease (n ​= ​1). The cumulative size of targeted lesions shrank by 4.8%–45.3% in 5 patients. R0/R1 resection was achieved in 6 (85.7%) patients. Postoperative complications (IId) were reported in 2 (28.6%) patients. There were no delayed post-operative complications. Median follow-up was 11.8 months. Median time-to-progression and median post-operative progression-free survival were not reached. Four patients who did not progress before surgery had no evidence of disease. Conclusion: Ripretinib combined with CRS is safe and effective in select patients with advanced GIST despite extensive prior therapy.